2007
DOI: 10.1038/ng2087
|View full text |Cite
|
Sign up to set email alerts
|

On the subspecific origin of the laboratory mouse

Abstract: The genome of the laboratory mouse is thought to be a mosaic of regions with distinct subspecific origins. We have developed a high-resolution map of the origin of the laboratory mouse by generating 25,400 phylogenetic trees in 100 kb intervals spanning the genome. On average 92% of the genome is of M. m. domesticus origin and the distribution of diversity is strikingly non random among the chromosomes. There are large regions of extremely low diversity, representing blind spots for studies of natural variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
356
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(377 citation statements)
references
References 44 publications
20
356
0
1
Order By: Relevance
“…Admixture between subspecies of the house mouse (Mus musculus) has been the subject of classical hybrid zone analyses [38,39] and offers great potential for future analysis, particularly given the genome resources for the species [48]. Similarly, existing laboratory mouse lines might provide a suitable recombination history for admixture mapping of isolating factors and other trait variation [49,50], as the genomes of laboratory mouse lines are largely derived from admixture between domesticus and musculus subspecies of M. musculus [51]. However, whether sufficient recombination for fine-scale mapping has occurred remains unclear [52][53][54].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Admixture between subspecies of the house mouse (Mus musculus) has been the subject of classical hybrid zone analyses [38,39] and offers great potential for future analysis, particularly given the genome resources for the species [48]. Similarly, existing laboratory mouse lines might provide a suitable recombination history for admixture mapping of isolating factors and other trait variation [49,50], as the genomes of laboratory mouse lines are largely derived from admixture between domesticus and musculus subspecies of M. musculus [51]. However, whether sufficient recombination for fine-scale mapping has occurred remains unclear [52][53][54].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 99%
“…High-throughput methods for sequencing and nucleotide polymorphism detection are making it possible to detect variation at nearly 10 7 molecular markers in some species of interest [48,51]. Clearly, analysis at this scale generates new demands on computational efficiency and interpretability of results.…”
Section: Box 4 Sampling Distributions Of Admixed Individualsmentioning
confidence: 99%
“…Willse et al (2006) examined the urinary volatile metabolic profiles of two MHC haplotypes (H2 b and H2 k ) and their heterozygous cross (H2 b  H2 k ) in two different background strains (B6 and BALB/c). Although a large proportion of the background genes are shared between these strains, thereby limiting potential between-strain genetic variability, substantial genetic variation is observed that is mainly derived from the variability in founders from the main wild source, Mus musculus domesticus (Yang et al 2007). In this study, we used a different method of isolation for volatile compounds: solid phase microextraction (SPME) headspace analysis, followed by GC/MS and statistical analyses.…”
Section: Chemical Investigations Of Mhc Odourtype In Micementioning
confidence: 99%
“…Virtually all classical laboratory mouse strains are derived from small founder populations and have been made genetically uniform (that is, homozygous for all genetic loci), hence facilitating experimental consistency and reproducibility. However, this artificial selection has resulted in a striking lack of genetic diversity in laboratory mouse models compared with natural animal populations, and has substantially reduced the genetic complexity of quantitative traits [8][9][10][11][12] . In addition, most laboratory mouse strains are the product of decades of artificial selection, both deliberate and inadvertent, that selected specific traits promoting reproductive success under laboratory conditions.…”
mentioning
confidence: 99%